Loss Of Excitation (LOE) Protection of Synchronous Generator - Hui Hwang Goh; Sy yi Sim; Mohd. Nasri Abd Samat; Ahmad Mahmoud Mohamed; Chin Wan Ling; Qing Shi Chua; Kai Chen Goh (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
Synchronous generators require certain protection against loss of excitation because it can lead to harmful effect to a generator and main grid. Systems of powers are evolving with applications of new techniques to increase reliability and security, at the meantime techniques upgradation is being existed to save financial cost of a different component of power system, which affect protection ways this report discuss the way of loss of excitation protection scheme for an increase in a synchronous generator. It is obvious that when direct axis synchronous reactance has a high value, the coordination among loss of excitation protection and excitation control is not effective. This lead to restricting absorption capability of the reactive power generator. This report also reviews the suitable philosophy for setting the limiters of excitation and discusses its effect on loss of excitation protection and system performance. A protection scheme is developed to allow for utilization of machine capability and power swing blocking is developed to increase the reliability when power swing is stable.